Indoor black carbon of outdoor origin and oxidative stress biomarkers in patients with chronic obstructive pulmonary disease. (June 2018) - Grady, Stephanie T.; Koutrakis, Petros; Hart, Jaime E.; Coull, Brent A.; Schwartz, Joel; Laden, Francine; Zhang, Junfeng (Jim); Gong, Jicheng; Moy, Marilyn L.; Garshick, Eric
Abstract: Objectives: We assessed relationships between indoor black carbon (BC) exposure and urinary oxidative stress biomarkers, 8-hydroxy-2′-deoxyguanosine (8-OHdG) and malondialdehyde (MDA), in participants with chronic obstructive pulmonary disease (COPD). Methods: Eighty-two participants completed in-home air sampling for one week prior to providing urine samples up to four times in a year. Weekly indoor and daily outdoor concentrations were used to estimate indoor daily lags and moving averages. There were no reported in-home BC sources, thus indoor levels closely represented outdoor BC infiltration. Mixed effects regression models with a random intercept for each participant were used to assess relationships between indoor BC and 8-OHdG and MDA, adjusting for age, race, BMI, diabetes, heart disease, season, time of urine collection, urine creatinine, and outdoor humidity and temperature. Results: There were positive effects of BC on 8-OHdG and MDA, with the greatest effect the day before urine collection (6.9% increase; 95% CI 0.9–13.3%, per interquartile range: 0.22 μg/m 3 ) for 8-OHdG and 1 to 4 days before collection (8.3% increase; 95% CI 0.03–17.3% per IQR) for MDA. Results were similar in models adjusting for PM2.5 not associated with BC and NO2 (10.4% increase, 95% CI: 3.5–17.9 for 8-OHdG; 8.1% increase, 95% CI: −1.1–18.1 for MDA). Effects on 8-OHdG were greater in obese participants. Conclusions: We found positive associations between BC exposure and 8-OHdG and MDA, in which associations with 8-OHdG were stronger in obese participants. These results suggest that exposure to low levels of traffic-related pollution results in lipid peroxidation and oxidative DNA damage in individuals with COPD. Highlights: Black carbon samples in participant homes were collected up to four times a year. Indoor black carbon represents infiltration of outdoor traffic-related particles. Participants provided urine samples after each environmental sampling. Indoor exposures are positively related to urinary oxidative stress biomarkers.